THE ROLE OF PARASYMPATHETIC AUTONOMIC REGULATION IN ENSURING OF RATS’ RESISTANCE IN THE MODEL OF MULTIPLE ORGAN DYSFUNCTION SYNDROM - Khrypachenko, I. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
To assess contribution of autonomic regulation in multiple organ dysfunction syndrome (MODS) survival ensuring and to test hypothesis about possible correction of clinical course by modulating the activity of parasympathetic influences we performed experiments on rats’ model of the MODS. It was determined that nonresistant animals differentiated by less intensity of parasympathetic regulation response. It was revealed that stimulation of cholinergic system decrease lethality in rats, and inhibits the power of high frequency regulatory effects on the heart rate.